Determination of polycyclic aromatic hydrocarbon metabolites in urine of coke oven workers in Turkey and exposure assessment - İçli, Nesrin; Kayaalti, Zeliha; Söylemezoğlu, Tülin (Informa UK Limited, 2021)
Coke-oven workers are occupationally exposed to high concentrations of polycyclic aromatic hydrocarbons. In this study, 1-hydroxypyrene, 9-hydroxyphenantrene, and 3-hydroxybenzo[a]pyrene levels wer...
Keywords: 13. Climate action; 11. Sustainability; 3. Good health